THE EFFECT OF WATERING INTERVAL ON GROWTH AND RESULT OF TWO VARIETIES OF Glutinous Rice (Oryza Sativa L. Var. Glutinosa) - Septian Widhiarto (AGRONISMA, 2022)
National sticky rice consumption during the last five years (2014-2018) tends to increase by 19.10% per year (BPS, 2018). Rice irrigation water management is very important to maximize the development of rice cultivation technology, especially to improve water use efficiency. This study aims to determine the effect of water application intervals on the growth and yield of several varieties of glutinous rice (Oryza sativa L. Var. Glutinosa). This research was carried out in March - July 2021 at the Green house of the Faculty of Agriculture in this location, which is located at an altitude of 550 meters above sea level with an average temperature of 270C-300C. The experiment used a factorial randomized block design (RAK) consisting of 2 factors. The first factor: interval of water supply consisting of 3 levels I0 (watered every day), I1 (watered every 6 days), I2 (watered every 12 days). The second factor is plant variety which consists of 2 levels: V1 = Siem variety (white), V2 = Payaman variety (black). The results data were tested with the BNT test (Least Significant Difference) at 5% level. Based on the ANOVA results, there was no significant interaction with plant height, number of leaves, number of tillers and leaf area. In each treatment, the best growth rate and yield between watering intervals and two varieties of glutinous rice (Oryza sativa L. Var. Glutinosa) were not found